Zooarchaeological reconstruction of newly excavated Middle Pleistocene deposits from Elandsfontein, South Africa. (February 2018) - Forrest, Frances L.; Stynder, Deano D.; Bishop, Laura C.; Levin, Naomi E.; Lehmann, Sophie B.; Patterson, David B.; Matthews, Thalassa; Braun, David R.
Abstract: The current study provides the first zooarchaeological account of systematically excavated faunal material from Elandsfontein, South Africa (ca. 1.0–0.6 Ma). Archaeological assemblages of this age typically lack well-preserved faunal remains recovered in primary association with artifacts, and thus studies have primarily focused on lithic technology. The sizeable faunal sample from Elandsfontein, South Africa is a rare exception and has dramatically influenced the way that we interpret early hominin foraging behavior during this time. Surface collections, starting in the 1950s, recovered 13, 000 mammalian fossils and > 160 Acheulean artifacts. The Elandsfontein faunal assemblage was interpreted as having accumulated through natural mortality and subsequent scavenging by carnivores and hominins, with hominins playing a very minimal role in carcass modification. Low frequencies of stone tool cutmarks were taken as evidence that Acheulean hominins had limited ability to obtain large carcasses. However, this interpretation contrasts with a growing body of evidence suggesting that many Acheulean hominins across sub-Saharan Africa not only had access to large mammal carcasses but were often the primary agents of accumulation and modification. The majority of the original Elandsfontein faunal material was collected from deflation surfaces and lacks sufficient contextual information. We conducted a detailed zooarchaeological analysis of faunal remains from four recent excavations within the Elandsfontein dune field. Our results differ from those based on surface collections and suggest multiple agents of bone accumulation with varying degrees of hominin and carnivore activity across the paleolandscape. Frequencies of hominin-induced butchery are higher (up to 3.6% NISP) than reported for previously collected samples (< 1% of limb surfaces) and demonstrate butchery of megafauna on at least two occasions. Our findings indicate that earlier zooarchaeological studies at Elandsfontein underestimate the degree of hominin contribution to the fossil assemblage and do not take into account the complicated taphonomic history across the paleolandscape. The results of this analysis are congruent with recent studies suggesting that Acheulean hominins and their Oldowan producing predecessors had regular access to large carcasses and that megafauna were an essential component of the diet for early Homo . Highlights: First zooarchaeological account of systematically excavated faunal material from Elandsfontein, South Africa. Frequencies of hominin-induced butchery are higher than reported for previously described surface collections. Demonstrates butchery of megafauna on at least two occasions. Varying degrees of hominin and carnivore activity across the paleolandscape.